Pola Spritual Dan Intelektual Lulusan Pondok Pesantren Al-Qur'an Al-Majidiyah Bagan Batu - Sari, Ratna; Dawud Faza, Abrar M (Jayapangus Press, 2024)
Alumni of Islamic boarding schools sometimes use their time and habits to engage in unproductive activities, such as dating, and there are even female students who participate in bullying. This problem raises questions about whether the teachings imparted by the pesantren and the actions taken by its students are in alignment with each other. Why do individuals who graduate from institutions designed to impart religious and spiritual principles often engage in negative behaviors? The aim of this research is to obtain an overview of the religious practices and religious knowledge of the alumni of the Al-Qur'an Al-Majidiyah Islamic boarding school in Bagan Batu. This research uses a qualitative methodology, employing interviews, documentation, and observation to collect descriptive data. The research findings indicate two themes to describe the religious practices and religious knowledge of alumni from Islamic boarding schools. These themes relate to the conditions while living in boarding school and after leaving. The research subjects are alumni of Islamic boarding schools who have made changes that are not in accordance with Islamic teachings. This study shows that students who graduated from the Al-Majidiyah Islamic boarding school still have a thorough understanding of religious practices and their religious knowledge. In addition, they still often practice their religion.